Exosomes Derived From Mesenchymal Stromal Cells Pretreated With Advanced Glycation End Product-Bovine Serum Albumin Inhibit Calcification of Vascular Smooth Muscle Cells - Wang, Ying; Ma, Wen-Qi; Zhu, Yi; Han, Xi-Qiong; Liu, Naifeng (Frontiers in Endocrinology, 2018)
Background The osteogenic differentiation of vascular smooth muscle cell (VSMCs) is important for the development of vascular calcification (VC), particularly in diabetes. Exosomes derived from Mesenchymal Stromal Cells (MSCs) are effective against cardiovascular diseases, yet their role in VC remains unclear. Advanced glycation end products (AGEs) inhibit bone marrow stromal cell osteogenesis by targeting osteogenesis-associated genes. Thus, we investigated the role of exosomes derived from MSCs pretreated with AGE-BSA in VC and its potential mechanisms. Methods Primary VSMCs and MSCs were isolated from the aorta and bone marrow of Sprague-Dawley rats, respectively. VSMCs were cultured with AGEs-BSA to induce osteogenic differentiation. Exosomes were harvested from MSCs by ultracentrifugation. MSCs and VSMCs were cocultured in Transwells, and exosomes were added to VSMC culture medium to assess their effects on osteogenic differentiation. Double luciferase reporter assay was applied to confirm that miR-146a directly targets the 3' UTR of the thioredoxin-interacting protein (TXNIP) gene. Results Pretreatment of VSMCs with AGEs-BSA increased the expression of thioredoxin-interacting protein (TXNIP) by inhibiting that of miR-146a, resulting in enhanced ROS production and VSMC calcification. By contrast, the expression of miR-146a in MSCs was increased by AGEs-BSA treatment. Thus, miR-146a was transferred from AGEs-BSA-pretreated or miR-146a-transfected MSCs to VSMCs via exosomes. After coculture with miR-146a-containing exosomes, the AGEs-BSA-mediated increase in VSMC calcification was diminished, accompanied by decreased TXNIP expression and ROS production. Furthermore, TXNIP overexpression counteracted the anti-calcification effects of MSC-derived miR-146a-containing exosomes. In addition, TXNIP was identified as a target gene of miR-146a, and the results of double luciferase reporter assay confirmed that TXNIP was the direct target gene of miR-146a. Conclusions Exosomes secreted by MSCs pretreated with AGE-BSA contained a high level of miR-146a, which was transferred to VSMCs and inhibited AGEs-BSA-induced calcification in a TXNIP-dependent manner. Thus, miR-146a-containing exosomes may be a potential therapeutic target for VC.